Instability behavior of arches under quasi-static concentrated load - Kien, Nguyen Dinh (Vietnam Journal of Mechanics, 2005)
The present paper investigates the instability characteristics of arch structures under quasi-static concentrated load. The arches are idealized as equivalent frameworks and analyzed by the finite element method using the nonlinear co-rotational beam elements. The numerical algorithms for computing the limit load and tracing the equilibrium path are presented. In particular, the automatic cutting and automatic increment techniques needed for the incremental/iterative procedure are described in detail. The effects of geometry, boundary condition, shear deformation, loading condition as well as the material characteristics on the instability behavior of both the elastic and elasto-plastic arches are numerically investigated.